LOAD EXTRACTION OF LEAF-SPRING BUSHING BASED ON ROAD LOAD DATA AND TEST-RIG FATIGUE TEST - GE WenTao; GONG ChunHui; LIU Zhou; DUAN LongYang; HUANG Hui (Jixie qiangdu)
In order to validate the durability attribution of leaf-spring rubber bushing fast and effectively,with the inputs of six-component force from proving ground,and taking rear suspension multi-body model as a carrier,based on the road load data,by applying virtual iteration technique,the dynamic load of bushing has been extracted. In order to keep the connection between the test-rig and the road of proving ground,according to equivalent damage theory,the fatigue test procedure of test-rig has been draw up by using multi-block fatigue load method,and the time consuming of test-rig has been shortened,and acceleration factor of 5. 03 was achieved by comparing the test time of test-rig and proving ground,the bushing has ultimately passed the durability validation of test-rig.